Increased Success in Exclusive Breastfeeding with the Use of Guidelines for Lactation Cadre Assistance - Teta Puji Rahayu; Tinuk Esti Handayani; Rahayu Sumaningsih (Knowledge Dynamics, 2025)
Background: The support of health cadres plays an important role in the success of the exclusive breastfeeding program. Health cadres have been widely involved in various activities carried out in the village, especially for maternal and child health programs, but for lactation cadre assistance to postpartum mothers is still not active because there are no lactation cadre assistance guidelines that can be used. The purpose of this study is to develop guidelines for assisting lactation cadres and assess their effectiveness in increasing the success of exclusive breastfeeding. Methods: This research is a Research and Development (R&D) research, starting with a literature study by studying journals and books related to health cadres and Exclusive Breastfeeding. Compile guidelines for assisting lactation cadres from the results of development. Data was collected using a questionnaire through FGD together with 50 health cadres, 2 village midwives and 3 representatives from the Magetan Regency Health Office, expert consuls followed by the revision and finalization of lactation cadre assistance guidelines. Results: This research produced guidelines for assisting lactation cadres, the results of the evaluation of guidelines for assisting lactation cadres through the process of development, formulation of strategic issues, and FGD. Conclusions: The guidebook for lactation cadres is a strategic step in supporting the success of the Exclusive Breastfeeding program so that it can increase the success of Exclusive Breastfeeding in the community.